Thermochemical battery prototypes with conductive heat extraction - Desage, Lucie; Humphries, Terry; Paskevicius, Mark; Buckley, Craig (2024)
Thermochemical energy storage is a viable option for large-scale storage of renewable energy. Functional storage systems require a high cycling capacity and an efficient heat extraction unit to guarantee reliable energy storage and subsequent power production. This article investigates the performance of thermochemical battery prototypes that use conductive heat extraction via metallic rods. The thermodynamics and kinetics of the storage material, CaCO3-Al2O3 (20 wt%), used in the prototypes, were studied along with the cyclic carbon dioxide sorption capacity, which was retained at 60 %. The reaction thermodynamics and kinetics of this doped CaCO3 compound are similar to those reported for pure calcium carbonate (ΔHdes = 173 ± 10 kJ.mol−1 CO2 and ΔSdes = 147 ± 9 J.mol−1 CO2·K−1). The two prototypes were constructed using either a stainless-steel rod or a stainless-steel tube with a copper core as conductive heat exchanger. The thermochemical battery prototypes (∼1 kg) cycled >30 times, with thermal charging (calcination) and discharging (carbonation) at ∼900 °C. The storage material is sensitive to the operating conditions of pressure and temperature, which influence the formation of various calcium aluminium oxide compounds that either catalyse or inhibit the cyclic capacity. The carbon dioxide sorption capacity in the prototypes was found to be limited (20 %) and capacity loss was correlated to the temperature distribution through the storage material and limited by the heat transfer rate of the heat extraction system. The heat transfer performance of the stainless-steel rod was inadequate, while the copper core allowed for better system performance.